Analisis Keterlambatan Proyek Jalur Pejalan Kaki (Studi Kasus: Jalur Pedestrian Jalan Kandang Roda – Pakansari) - Rosa Kartika Maharani; Suwandari Dian Yunita (Jurnal Teknik Sipil, 2021)
The purpose of Kandang Roda – Pakansari Pedestrian Project is to supporting pedestrians to be more comfortable, safe and also to make the face of the capital city of Bogor Regency be more attractive for tourism. The purpose of research is to identify major factors that contribute the most on project delays. The research is using quantitative methods and questionnaire towards the employee of DINAS PUPR Bogor Regency as the owner and the employee of PT. Vanca Utama Perkasa as the main contractors. The questionnaire will be collected using SPSS software. The research is required to avoid similar fault and causing many loss. The results of research said that Environment Factor (X.6) is being the major factor that affect delays on this project according to Statistic Descriptive Analysis test. The factor had 4.00 mean bigger than others, with Availability of utilities (cables); PLN, Telkom, PDAM, Fiber Optic which are underground as the indicato (X6.11). The result is support by T Test with a probability value of 0.0000 which means that partially there is a significant influence between these variables and project delays